INDONESIAN CIVIL ENGINEERING STUDENTS’ METACOGNITIVE AWARENESS DURING INDEPENDENT ENGLISH SPEAKING CLUB ACTIVITIES - Tabita Hermayani; Concilianus Laos Mbato (IKIP Siliwangi, 2020)
The global market’s growth influences the increasing need of English speaking proficiency for many professions. Hence, non-English department students equip themselves with English speaking proficiency. Some take courses in some informal institutions; others make their own independent English club. A group of metacognitive Civil Engineering students in Indonesia formed a Speaking Club to facilitate their learning. The research aimed to measure the metacognitive awareness of some Civil Engineering students during their independent learning activities. The analysis was done by using the Metacognitive Awareness Inventory (MAI). To triangulate the data, interviews, observation and critical reflection were used. From the research it could be concluded that independent learning can be facilitated and born from cooperative learning. Cooperative learning builds up learners’ motivation through peer feedbacks and monitoring done by a tutor. Metacognitive awareness was built upon the realization of clear learning objectives, followed by self-determination, and planning. Consistency is also required to sustain self-regulated learning. Keywords: Metacognitive Awareness, Speaking, Learning Strategy